Returning to judgment Bernard Stiegler on technics, totalization, and the limits of political ontology - Turner, Ben (Political theory lecturer) (Albany, NY : State University of New York Press, 2023)
"Returning to Judgment" provides the first extensive treatment of political judgment in the work of Bernard Stiegler and the first account of his significance for contemporary continental political thought. Ben Turner argues that Stiegler breaks with his predecessors in continental philosophy by advocating for, rather than retreating from, the task of proposing totalizing judgments on political problems that extend beyond the local and the particular. He shows that the reconciliation of judgment with continental political thought's commitment to anti-totalization structures the entirety of Stiegler's philosophy and demonstrates that this theory of the political decision highlights the difficulties that contemporary political ontology faces when addressing global and large-scale political problems. The book provides an overview of Stiegler's philosophy useful for those unfamiliar with his thought, shows how he draws on key influences including Deleuze, Derrida, Freud, and Simondon to develop his conception of judgment, and considers the challenges and consequences of his embrace of totalizing political decisions.
eBooks on EBSCOhost
Keywords: Stiegler, Bernard -- Political and social views; Stiegler, Bernard; Political science -- Philosophy; Ontology -- Political aspects; Ontologie -- Aspect politique; Political and social views; Political science -- Philosophy